The role of environmental variables in structuring landscape‐scale species distributions in seafloor habitats - Casper Kraan; Geert Aarts; Jaap van der Meer; Theunis Piersma (Ecology, 2010)
Ongoing statistical sophistication allows a shift from describing species' spatial distributions toward statistically disentangling the possible roles of environmental variables in shaping species distributions. Based on a landscape‐scale benthic survey in the Dutch Wadden Sea, we show the merits of spatially explicit generalized estimating equations (GEE). The intertidal macrozoobenthic species, Macoma balthica , Cerastoderma edule , Marenzelleria viridis , Scoloplos armiger , Corophium volutator , and Urothoe poseidonis served as test cases, with median grain‐size and inundation time as typical environmental explanatory variables. GEEs outperformed spatially naïve generalized linear models (GLMs), and removed much residual spatial structure, indicating the importance of median grain‐size and inundation time in shaping landscape‐scale species distributions in the intertidal. GEE regression coefficients were smaller than those attained with GLM, and GEE standard errors were larger. The best fitting GEE for each species was used to predict species' density in relation to median grain‐size and inundation time. Although no drastic changes were noted compared to previous work that described habitat suitability for benthic fauna in the Wadden Sea, our predictions provided more detailed and unbiased estimates of the determinants of species–environment relationships. We conclude that spatial GEEs offer the necessary methodological advances to further steps toward linking pattern to process.